Development and validation of RME-based monopoly game for enhancing mathematical sentence problem-solving in primary school students - Tanaya Rizkika; Deni Adi Putra; Holy Ichda Wahyuni (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2026)
This study aimed to develop and evaluate the feasibility of a Monopoly-based learning media integrated with Realistic Mathematics Education (RME) to improve elementary students’ understanding of mathematical sentence problems. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The study was conducted with 18 third-grade students at an elementary school in Surabaya, Indonesia. Data were collected through expert validation sheets, teacher and student questionnaires, interviews, and pre-test and post-test assessments. Data analysis used descriptive quantitative techniques, including percentage and mean scores to determine validity, practicality, and effectiveness. The developed Monopoly Math Adventure media obtained a validity score of 92%, categorized as highly valid. The practicality level reached 82% based on teacher responses and 94% based on student responses, indicating a very practical category. The effectiveness analysis showed a classical learning completeness of 83%, demonstrating that the media significantly supported students’ learning outcomes in mathematical sentence comprehension. The integration of RME principles into a Monopoly-based learning game provides an effective and engaging instructional medium for elementary mathematics learning. The developed media is valid, practical, and effective, and it has strong potential to enhance students’ conceptual understanding of mathematical sentence problems in primary education contexts.